Предмет: Алгебра,
автор: Kunaizer
Помогите пожалуйста срочна заранее спасибо
Приложения:
![](https://files.topotvet.com/i/0a7/0a7f0c711f221e17f9ec7b996e5a7d98.png)
![](https://files.topotvet.com/i/99c/99ca0feb77c10bf3fa523fbb1f29fb00.png)
Ответы
Автор ответа:
0
2) (a^2(a-1)-(a-1))/(a^2-1)^2=
((a-1)(a^2-1))/(a^2-1)^2= (a-1)/(a^2-1);
4) (x(x-a)+b(x-a))/(x^2(x+b)+a(x+b))=
((x-a)(x+b))/((x+b)(x^2+a))= (x-a)/(x^2+a).
((a-1)(a^2-1))/(a^2-1)^2= (a-1)/(a^2-1);
4) (x(x-a)+b(x-a))/(x^2(x+b)+a(x+b))=
((x-a)(x+b))/((x+b)(x^2+a))= (x-a)/(x^2+a).
Похожие вопросы
Предмет: Химия,
автор: zcom2113
Предмет: Право,
автор: luchkinslava
Предмет: Математика,
автор: artemdolgoruk0
Предмет: Биология,
автор: sv160981